A decomposition method for form-finding of circular hybrid cable-truss structures considering self-weight - Wang, Zhenhua; Zhang, Zhihong; Peng, Zhangli; Wang, Xinran; Chen, Jiankai; Hu, Xinzan (Journal of constructional steel research, 2025)
A hybrid cable-truss structure has been previously utilized in the Maracana Stadium. There are two ways to design the initial prestress distribution in the hybrid cable-truss structure, taking into account the functionality of the upper and lower hoop cables. This study proposes a decomposition method for determining the form-finding of circular hybrid cable-truss structures with two different prestress distributions. The hybrid cable-truss structure is decomposed into the inner and outer cable-truss structures. The PBS (partial balance strategy) method is employed to design the prestress and shape of both the inner and outer cable-truss structures with consideration of self-weight. A detailed prestress and shape design analysis of a circular hybrid cable-truss structure with two prestress distributions is conducted, and the precision of the initial prestress design is analyzed. The illustrative example presented herein demonstrates that the proposed method, combined with the PBS method, provides a simple and accurate approach for the form-finding of hybrid cable-truss roof systems subject to self-weight. •A decomposition method for form-finding of circular hybrid cable-truss structures is proposed.•The decomposition method splits the hybrid cable-truss into the inner and outer cable-truss.•There are two prestress distributions in the hybrid cable-truss, considering the functionality of the middle hoop cables.•The decomposition method combined with the PBS method is accurate and efficient in determining prestress.•Considering self-weight is pivotal in the prestress design of the hybrid cable-truss structures.